Could secondary prevention of coronary heart disease be more effective? - V. I. Makolkin (Кардиоваскулярная терапия и профилактика)
Beta-adrenoblockers (BAB) in secondary prevention of coronary heart disease (CHD) are not always effective, due to non-achieved target heart rate (HR). The reasons for that could include medication intolerance, baseline bradycardia (HR<55 bpm), II-III Stage atrio-ventricular blocks, and acute episodes of generalized weakness when HR is reduced. In these situations, BAB could be effectively combined with ivabradine (10-15 mg/d). This combination provides an opportunity to achieve target HR levels (60-55 bpm).